Evaluation of dietary intakes and supplement use in Paralympic athletes - Madden, R. F.; Shearer, J.; Parnell, J. (Nutrients, 2017)
Dietary intakes and supplement use in Paralympic athletes remains largely unexplored, and specialized recommendations are lacking. The aim of this study was to evaluate nutrient intakes and supplement use in high-performance athletes with physical disabilities using three-day food records and a validated dietary supplement use questionnaire. A secondary aim examined gender differences in nutrient and supplement intakes. Male (n = 18) and female (n = 22) athletes were recruited from nine Paralympic sports through sporting organizations, coaches, and social media. Athletes generally met able-bodied recommendations for macronutrients. Male and female athletes often failed to meet the Recommended Dietary Allowance (RDA) or Adequate Intake (AI) for vitamin D, vitamin E, pantothenic acid, magnesium, and potassium. On average, females did not meet the RDA for iron and calcium, whereas males did not meet the RDA for vitamin A and folate. Commonly consumed supplements were vitamin D, protein powder, sport bars, and sport drinks. Analysis of diet and supplement use within this population shows several micronutrient deficiencies and irregular use of specific supplements. Athlete support and education is required to optimize nutrition in Paralympic athletes.